1993
DOI: 10.1002/jemt.1070260103
|View full text |Cite
|
Sign up to set email alerts
|

3D‐structure of cells of human salivary glands as seen by SEM

Abstract: To demonstrate by SEM the topography and cytoarchitecture of the different parenchymal components of human salivary glands, we have employed a number of techniques that allow either the exposure of internal and lateral cell surfaces or, following the removal of connective tissue, the visualization of endpieces, ducts, and myoepithelial cells. Serous glands consist of indented acini attached to the ducts in a grape-like fashion, whereas mucous and mixed glands are made up of smooth tubuli. Myoepithelial cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…Myoepithelial cells have several tapering processes containing actin and myosin filaments (Drenckhahn et al 1997;Redman et al 1980;Longtine et al 1985;Gugliotta et al 1988;Lazard et al 1993;Redman 1994;Satoh et al 1994;Segawa 1994;Deugnier et al 1995) and line the acini and ducts of exocrine glands, such as the salivary gland, mammary gland, sweat gland and lacrimal gland (Shear 1966;Garrett and Emmelin 1979;Nagato et al 1980;Pinkstaff 1980;Nagashima and Ono 1985;Riva et al 1988Riva et al , 1993Satoh et al 1994). On the basis of their structure and location in acini and ducts, myoepithelial cells are considered to play some roles in excretion or secretion (Shear 1966;Garrett and Emmelin 1979;Nagato et al 1980;Redman 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Myoepithelial cells have several tapering processes containing actin and myosin filaments (Drenckhahn et al 1997;Redman et al 1980;Longtine et al 1985;Gugliotta et al 1988;Lazard et al 1993;Redman 1994;Satoh et al 1994;Segawa 1994;Deugnier et al 1995) and line the acini and ducts of exocrine glands, such as the salivary gland, mammary gland, sweat gland and lacrimal gland (Shear 1966;Garrett and Emmelin 1979;Nagato et al 1980;Pinkstaff 1980;Nagashima and Ono 1985;Riva et al 1988Riva et al , 1993Satoh et al 1994). On the basis of their structure and location in acini and ducts, myoepithelial cells are considered to play some roles in excretion or secretion (Shear 1966;Garrett and Emmelin 1979;Nagato et al 1980;Redman 1994).…”
Section: Introductionmentioning
confidence: 98%
“…These ducts consist principally of tall columnar epithelial cells whose bases are interlocked in a highly complex fashion (Riva et al, 1993) to form a series of basal compartments in which elongated mitochondria reside, the folded plasma membranes and vertically oriented mitochondria being responsible for the ''basal striations.'' These ducts, working in concert with the excretory ducts (Schneyer et al, 1972), are thought to be major sites of electrolyte resorption from the isotonic primary saliva, so that the final saliva that reaches the mouth is hypotonic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a newly introduced procedure (RIvA et al, 1993a) for the study of bioptical material by the 0504 maceration method (TANAKA and MITSUSHIMA, 1984) provides more details on the three-dimensional shape and arrangement of cellular organelles even in human tissues. With these improved procedures, new information has been added recently to the three-dimensional architecture of human salivary glands (RIVA et al, 1991(RIVA et al, , 1993bRIvA, 1992). In particular, RIvA et al (1993b) report that cells of each glandular segment possess their own three-dimensional microanatomy, and suggest that they may play a distinct, particular role in the mechanisms of saliva production.…”
Section: Discussionmentioning
confidence: 99%
“…With these improved procedures, new information has been added recently to the three-dimensional architecture of human salivary glands (RIVA et al, 1991(RIVA et al, , 1993bRIvA, 1992). In particular, RIvA et al (1993b) report that cells of each glandular segment possess their own three-dimensional microanatomy, and suggest that they may play a distinct, particular role in the mechanisms of saliva production. In experimental animals, micropuncture studies have in fact demonstrated that salivary glands have portions endowed with different transport properties (SCHNEYER et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation